1997
DOI: 10.3386/w6060
|View full text |Cite
|
Sign up to set email alerts
|

The Gold Standard and the Great Depression

Abstract: !qqM © UOCC 12 AGU O iJJC 2OflLCC cxcccq jnn JxrwL&bp urnA pc drrnfcq itrporij cxbjicrj bctmiaarou bLoAIqcq jjrn ij cLcqu © JÔÔX P' 11SIA E!CPGUELGGU miq LG4GL J,GUJIU l'Jj LIJJ2 LcacLAcq apoc 2CC4OU2 OjtGxe IJOt W flflG&R 01.E00U0m!G KC2CCW yioucwA yuA obiu oua cxbLcaacq w° oijpc SflWoi2 uq uo oIjJJc J4&pou&j JJ112 LLCL LU14 OJ,J4BEJc,2 LC2C9LCJJ bLoJrnn2 TU W© DCACIOLWGU{ opc yuJcLTc9u pcououA &uq .lmJG Toa, swpuqc qy osn T 020 j&aacprracua VACUJIG MVIIOI4VF BflKEVfl OL ECOI4O1AIIC J EEVI{GH ftOLJC!U MJDCL Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
121
0
9

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(133 citation statements)
references
References 0 publications
2
121
0
9
Order By: Relevance
“…In the first period under examination, the global monetary system was dictated by the 'gold standard,' which included movements of gold between central banks, as a response to international non-financial transactions (Eichengreen and Temin 1997). The aim of the gold standard was to secure price stability and constrain fiscal expansion, reflecting 'the mentality and the type of conduct of … economic elites' (ibid., p. 187).…”
Section: Fiscal Monetary Policy and Capital Mobilitymentioning
confidence: 99%
“…In the first period under examination, the global monetary system was dictated by the 'gold standard,' which included movements of gold between central banks, as a response to international non-financial transactions (Eichengreen and Temin 1997). The aim of the gold standard was to secure price stability and constrain fiscal expansion, reflecting 'the mentality and the type of conduct of … economic elites' (ibid., p. 187).…”
Section: Fiscal Monetary Policy and Capital Mobilitymentioning
confidence: 99%
“…Some modern students, including Eichengreen (1992), have concluded that the Fed erred in loosening its policy, it is difficult to find a plausible reason for a tighter policy.…”
Section: The Role Of the Federal Reservementioning
confidence: 99%
“…As Romer (1990) showed, households responded by reducing their consumption of semi-durables and dramatically their consumption of durables---products that required the intermediate goods shipped by the railroads. The banking panics and gold outflows reduced the money supply and the willingness and ability of banks to lend (Friedman and Schwartz, 1963;Bernanke, 1983;Eichengreen, 1992).…”
Section: 1mentioning
confidence: 99%